The use of blockchain in the organisation of annual general meetings: legal and technological challenges - Tamašauskas, Nedas; Tamulionytė, Luka (Vilnius University Open Series, 2023)
This article analyses the practical application of blockchain technology in the organisation of annual general meetings. The paper presents examples of the spreading application of the technology in foreign companies. In addition, it discusses the legal regulation of the organisation of annual general meetings in Lithuania, which is relevant for the practical application of the technology: authentication of shareholders and voting. Furthermore, the perspectives of blockchain technology in the Lithuanian market and its companies are reviewed.
Keywords: annual general meeting; blockchain technology; blockchain; authentication of shareholders; voting of shareholders